Proceedings of the 2005 Particle Accelerator Conference
DOI: 10.1109/pac.2005.1590995
|View full text |Cite
|
Sign up to set email alerts
|

RHIC BPM System Modifications and Performance

Abstract: Brookhaven Science Associates, LLC for the United States Department of Energy under Contract No. DE-AC02-98CHlO886 This is a preprint of a paper intended for publication in a journal or proceedings. Since changes may be made before publication, this preprint is made available with the understanding that it will not be cited or reproduced without the permission of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The RHIC BPM system [7], [8] consists in 160 23-cm cryogenic striplines per plane per ring. Most of the devices are made of by two opposite striplines oriented vertically or horizontally accordingly to the higher beta function.…”
Section: Localized Impedance Measurementsmentioning
confidence: 99%
“…The RHIC BPM system [7], [8] consists in 160 23-cm cryogenic striplines per plane per ring. Most of the devices are made of by two opposite striplines oriented vertically or horizontally accordingly to the higher beta function.…”
Section: Localized Impedance Measurementsmentioning
confidence: 99%
“…Operational experience at RHIC has also demonstrated that BPM readings can have large digital offsets, and these offsets can vary over time due to issues with aging gain and calibration relays [5]. BPMs in the 6-and 8-o'clock low-β IRs were modified to remove these relays during the 2004 shutdown period.…”
Section: Introductionmentioning
confidence: 99%